Applying surface-sensitive techniques to structural and chemical study of uncapped Sn-Sb-Te thin film : A density functional theory - based study - Bilovol, V. (2021)
We present here a combined experimental and theoretical study of the structural and chemical properties of polycrystalline Sn-Sb-Te film with nominal composition SnSb₂Te₄ grown by pulsed laser deposition technique on mylar substrate. From the experimental side, surface-sensitive techniques as x-ray photoelectron spectroscopy (XPS), grazing incidence x-ray diffractometry (GIXRD) and ¹¹⁹ᵐSn integral conversion electron Möβbauer spectroscopy (ICEMS) have been applied to the study of the film at room-temperature and under normal conditions of pressure. GIXRD showed that the Sn-Sb-Te film adopted a NaCl- type structure (Fm-3m), and in the detection limits, no other crystalline phase was revealed. ICEMS technique unambiguously indicated the coexistence of two different tin fractions: Sn(II), as expected for the SnSb₂Te₄ phase, and Sn(IV), suggesting oxidation of tin. Chemical in-depth profile obtained by means of XPS suggests the oxidation of all the constituent atoms at the topmost layers of the film and the progressive depletion of tin and antimony oxides going depth in the film. The in-depth atomic concentration profiles also reveals a notorious deficiency of Te in the sample. Theoretically, density functional theory-based calculations (assuming that the Sn-Sb-Te film adopts the Fm-3m structure) support the hypothesis that Te - vacancies sites are occupied by oxygen atoms during the natural oxidation process of Sn-Sb-Te film. Additionally, our calculations demonstrated that only the substitution of Te atoms by oxygen ones induces a semiconducting behavior of the otherwise metallic Sn-Sb-Te host.